Comparing Physical Therapy Accompanying Exercise with Only Exercise Treatments in Patients with Chronic Mechanical Low Back Pain - Özlem Yılmaz; Pınar Küçük Eroğlu; Fatma Gül Yurdakul; Yeşim Garip Çimen; Filiz Eser; Aslıhan Alhan; Hatice Bodur (Galenos Yayinevi, 2015)
Objective: Investigating and comparing the effects of exercise and physical therapy accompanying exercise treatments in patients with chronic low back pain. Materials and Methods: Twenty three patients with mechanical type low back existing more than 3 months were included one of the exercise or the physical therapy+exercise groups according to their application sequence. Both of the groups performed lumbar flexion and extension exercises, strengthening of the lumbar and abdominal muscle exercises and iliopsoas, hamstring and quadriceps stretching exercises two times a day for 14 days. The physical therapy group was given hot pack+therapeutic ultrasound+ interferential current for 10 days additionally. Degree of the low back pain was evaluated with visual analog scale (VAS), range of joint motion was evaluated with hand finger floor distance (HFFD) and Modified Schober test, functional status was evaluated with Modified Oswestry Low Back Pain Scale and quality of life was evaluated with Short form-36 (SF-36) before and a month after the treatments. Results: In both groups (exercise group: average age 59 years, 21 females, 2 males; physical therapy group: average age 60 years, 20 females, 3 males) pain intensity and HFFD decreased and Modified Schober increased, functionality recovered, pain and physical functions of SF-36 improved after the treatments. SF-36-physical role difficulty also improved in the exercise group. Decrease in pain, increase in HFFD andimproving of the functional status were all significantly more in the physical therapy group. There were no difference between the groups in terms of Modified Schober measurement and changes of the quality of life. Conclusions: Exercises and exercise+physical therapy are both effective in chronic low back pain. Successful results can be taken by addition of the physical therapy in patients who do not benefit sufficiently from exercise therapy. (Turkish Journal of Osteoporosis 2015;21: 73-8)